Preference Change
XII, 266 p.
Keywords: The fact that preferences change is a pressing but unresolved problem for philosophy and the social sciences. Social scientists use preferences to explain agents’ behaviour; philosophers use preferences to explicate value judgements. A lot of empirical research is invested into identifying people’s preferences. However, the success of these endeavours is seriously threatened, because precise accounts of when and why preferences change are lacking. This volume answers to this need by collecting new essays from an interdisciplinary group of experts in the field. These essays, especially written for this volume, survey the newest approaches to preference change developed in the social sciences and in philosophy, and will serve as a platform for future research. They review some standard material, including the neoclassical preference model and doxastic preference change, time preferences and the debate over policy evaluation under preference change. However, the focus is on new research that is not widely known, such as conditional utilities, non-monotonic logics, complex systems models, inter-temporal choice approaches, etc. The book serves three purposes. It introduces undergraduate students to the current state of research on preference change, it gives graduate students and researchers in-depth insights into the state-of-the-art modelling techniques of different disciplines; and it points out to experts the lacunae in the literature and directions for future research.